Concept maps: Empirical and academic knowledge for mangrove ecosystem - Carvalho da Silva, Amina; Pereira Tognella, Mônica Maria; Duarte-Silva, Erica (Guará Journal, 2018)
Critical and contextualized Biology Teaching Actions and Environmental Education are of paramount importance for the conservation of the Environment in general and the Mangrove ecosystem in particular. The objective of the research was to evaluate the knowledge about man-grove in two communities. One constituted by traditional population in Conceição da Barra - ES, and another by students of the Bachelor of Biological Sciences course. This study is ethnographic, and therefore exploratory. The methodology used was the systematic and direct observation associated with the collection of documentary data, with a temporal cut between 1980 and 2017. At the end, 15 conceptual maps were elaborat-ed to determine the degree of importance of the focal element, based on the list of assumptions obtained. The data obtained indicate that the species of crab (Ucides cordatus L., 1763) has great economic and cultural importance for the communities; both present environmental perceptions regarding the importance of the economic, social and environmental roles of the mangrove ecosystem. In relation to students, con-ceptions of conceptual maps reinforce the need for greater study of the environment, for apprehension of the theory by the Bachelor in Biological Sciences. With this, the actions of teaching in the graduation with ap-plications of different techniques should be intensified and the concep-tual map proved to be an excellent tool to evaluate the apprehension of the knowledge. The insertion of the Academy into extension actions with traditional communities may be a source of research, teaching, action and strengthen the social relations of the University, making it present in society.